Studies on Dry Matter Production and Efficiency for Solar Energy Utilization in Bupleurum falcatum L. at Different Plant Ages - Tae-Kwon Shon; Totok Agung Dwi Haryanto; Tomohiko Yoshida (Plant Production Science, 1998)
Two Bupleurum falcatum cultivars, which originated from Jeongseon, Korea and Kumamoto, Japan were grown for two years to clarify the dry matter (DM) production, efficiency for solar energy utilization (Eu) and saikosaponin a,c and d contents in Fukuoka, Japan. Aerial parts, root and total DM production differed with the cultivar both in the first and second years. Generally, DM production correlated with leaf area index, and there was a significant relationship between total DM and Eu in the plants of the first year in both cultivars. High Eu was observed at the flowering stage in both cultivars in both years. The maxium Eu was 1.02-1.23% in the first year and 1.16-2.09% in the second year. Total saikosaponin content was higher in the first year than in the second year. Although the total saikosaponin content was higher in Jeongseon cultivar than in Kumamoto cultivar in the second year, no difference betweeen the two cultivars was observed in the first year. We concluded that annual cultivation with a high saikosaponin content was preferable for the high yield of saikosaponin.